If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(2x + -1) = 27 + x Reorder the terms: 3(-1 + 2x) = 27 + x (-1 * 3 + 2x * 3) = 27 + x (-3 + 6x) = 27 + x Solving -3 + 6x = 27 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -3 + 6x + -1x = 27 + x + -1x Combine like terms: 6x + -1x = 5x -3 + 5x = 27 + x + -1x Combine like terms: x + -1x = 0 -3 + 5x = 27 + 0 -3 + 5x = 27 Add '3' to each side of the equation. -3 + 3 + 5x = 27 + 3 Combine like terms: -3 + 3 = 0 0 + 5x = 27 + 3 5x = 27 + 3 Combine like terms: 27 + 3 = 30 5x = 30 Divide each side by '5'. x = 6 Simplifying x = 6
| 7x+9y= | | 3y^2-147=0 | | 6(35)+.3x=450 | | 1/2(4d-2)=d+5 | | 9y^2+24y-20=0 | | 3-9m=18 | | -0.33(x+2)=7x+3 | | 15x^2-26x-57=0 | | -0.33.3(x+2)=7x+3 | | 4x+12+2x+7+14x-9=180 | | 5(2x+7)=5(4-x) | | 7(3x+4)=10-3x | | 25x(x+3)=8500 | | 15x^2-14x-57=0 | | x+1y=2x-1 | | g(1)=2(1)+4 | | 6a+6=4a-1 | | 3x-2+4x+x+12=66 | | 12x^2+18=30 | | mp+mq=r | | 3(x-4)=2(x-3) | | 21x-6+5=26 | | 5v-9=3v+1 | | 3(5-5)= | | 88=7x+5x+4 | | -12x+7=4x-9 | | 7v-9=4v+3 | | 81t^2-144t+64= | | 5(2+t)-2(t+1)= | | 6v-4=5v+4 | | 16s^2-56s+49= | | b=75+(15+6)w |